Effect of Xylanase Supplementation and Particle-Size on Performance of Guinea Fowl Broilers Fed Wheat-Based Diets - Tufarelli, V.; Dario, M.; Laudadio, V. (International Journal of Poultry Science, 2007)
The effect of xylanase enzyme supplementation and particle-size in wheat (Triticum durum)-based diets was studied in guinea broilers from 29 to 91 days of age. Weekly body weight, gain, feed consumption and Feed Conversion Ratio (FCR) were determined. Was formed 4 groups, each fed: diet A (ground wheat with enzyme); diet B (ground wheat without enzyme); diet C (ground wheat passed through 3 mm sieve, pelleted and after crumbled with enzyme): diet D (crumbled wheat without enzyme). The highest body weights values were recorded by guinea fowls fed diet C. Birds fed diet B have shown low mean values of body weight. Subjects fed diet C were obtained values of mean body weight different (p<0.05) respect to subjects fed both unsupplemented diets. Between two diets containing xylanase, even if prepared with different method, weren`t recorded differences (p<0.05), even if subjects fed crumbled diets show an increase of body weight in comparison to subjects that received ground diets. Body weight gain of guinea broilers fed diet A and diet B were recorded high values, with differences (p<0.05) in birds fed supplemented diets. These differences weren`t observed between birds fed diets B and D. Feed consumption showed that birds fed diets A and B consume an higher amount of feed (p>0.05) compared to the diets C and D, regardless the supplementation of xylanase. Within every typology of diet (ground versus crumbled) aren`t recorded differences (p<0.05) for the presence or not of enzyme, even if between crumbled diets, supplementation however has reduced feed consumptions. FCR of every diets shown`t differences (p<0.05) among them, with values in guinea broilers fed supplemented diets similar to data recorded in birds fed unsupplemented diets. The supplementation of xylanase in a crumbled wheat-based diet improved the growth performance of guinea fowl broilers.